Running scared - Foster, David; Turman, Lawrence; Hyams, Peter (MGM Home Entertainment, 1986)
Ray and Danny are the wild men of the Windy City's police force. The pair's worthodox methods get results in a tough town - until they come up against Julio Gonzales (Jimmy Smits, "NYPD Blue"), a smooth-talking drug dealer who is bucking to become Chicago's first Spanish Godfather. Trying to nail Gonzales, they blow a delicate undercover operation and are sent on a forced vacation to Key West - where they discover the good life of warm weather and warmer women. The new locale makes them decide to retire...but not before putting Gonzales behind bards first.